Efficacy of microbiological nematicides in controlling root-knot nematodes in tomato - Pontes, Karoline Barbosa; Machado, Andressa Cristina Zamboni; Nogueira, Alison Fernando; Fagundes, Daniel Fernando Viana; de Lima Filho, Renato Barros; Mosela, Mirela; Mian, Silas; Santiago, Débora Cristina; Gonçalves, Leandro Simões Azeredo (Frontiers in Agronomy, 2024)
Root-knot nematodes (RKNs) are considered a limiting factor for tomato production, causing substantial economic losses. Several control measures have been used to control RKNs in infested areas, such as crop rotation or succession with non-host species, using resistant cultivars, and applying chemical and biological nematicides. Here, we examined the control effect of six microbiological products (Ag109 - Bacillus velezensis, Votivo Prime - B. firmus, Quartzo - B. subtilis and B. licheniformis, Veraneio - B. amyloliquefaciens, Nemat - Purpureocillium lilacinum, and Rizotec - Pochonia chlamydosporia) against different species of Meloidogyne in tomatoes cultivated in a greenhouse and evaluated these products under field conditions to verify their impact on root-associated nematode populations and agronomic and physicochemical traits of fruits from grafted and non-grafted tomato plants. For the greenhouse studies, higher pathogenicity was observed for tomato with M. javanica and M. enterolobii compared to M. incognita. The microbiological nematicides were more effective in controlling M. javanica and M. enterolobii, while for M. incognita, the evaluated products were ineffective. Regarding the field studies, most of the microbiological nematicides evaluated effectively increased production per plant. However, when analyzing the Meloidogyne population in the field, applying microbiological nematicides showed no nematode control in plants without rootstock. On the other hand, in the grafted plants, the Ag109, Veraneio, Rizotec, and Nemat treatments boosted the reduction in the Meloidogyne population in the roots, with average reductions of 68.47, 57.97, 77.29, and 56.70%, respectively. These results indicate the effectiveness of integrated management of microbiological nematicides and resistant rootstock in tomato. Furthermore, combining these two control measures resulted in no change in the nutritional quality of tomato fruits.